RISK FACTORS, FETO-MATERNAL OUTCOMES, MANAGEMENT OPTIONS IN RUPTURE OF GRAVID UTERUS -AN OBSTETRIC CATACLYSM - Dr. Hemalatha C.R.; Dr. Ravi Sree Shivani (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Maternal Morbidity and mortality has been a major World Health Organisation concern over the years. Obstetric hemorrhage is one amongst the leading causes responsible for this. Uterine Rupture is a serious obstetric emergency associated with significant maternal and neonatal morbidity and mortality. The Objective of this paper is to identify the obstetric risk factors, incidence, causes, associated foeto-maternal outcomes and management options in patients of rupture uterus at a tertiary care centre in Mysore– Cheluvamba hospital.Method: A 3 year retrospective analysis of 28 cases of Uterine Rupture treated in our hospital between December 2019 to December 2022 was done. The case sheets of these patients were analysed and data regarding demographic characteristics clinical presentations, risk factors, management, operative findings, maternal and foetal outcomes, post-operative complications were studied and the data analysed.Results: The Incidence of uterine rupture was 0.1%. The vast majority of patients were referred from periphery(92.9%) with most common clinical symptom of abdominal pain (32.1%) with a clinical sign of sustained uterine contractions (39.3%). The most common risk factor was previous scarred uterus(67.9%), 46.4% cases underwent total hysterectomy as a management option. There were 3 maternal deaths and 9 cases delivered alive and healthy neonates.Conclusion: Uterine rupture is a preventable obstetric crisis linked to significant feto-maternal morbidity and mortality. The main causes are multiparity, obstructed labour, previous cessarean section and late referrals. Identification of these High risk women, Prompt diagnosis, Immediate referral and Optimal management can surely avoid adverse feto-maternal outcomes.